Omalizumab for Chronic Urticaria: A Case Series and Overview of the Literature - Ilya Ivyanskiy; Carsten Sand; Simon Francis Thomsen (Karger Publishers, 2012)
Omalizumab is a recombinant humanized monoclonal antibody that blocks the high-affinity Fc receptor of IgE. Omalizumab has been approved for the treatment of moderate to severe asthma; however, there is currently more and more data showing promising results in the management also of chronic urticaria. We present a case series of 19 patients with chronic urticaria treated in a university department with omalizumab and give an overview of the existing literature comprising an additional 59 cases as well as a total of 139 patients enrolled in two randomized controlled trials comparing omalizumab with placebo. The collective evidence points to omalizumab as a safe and effective treatment option for patients with chronic urticaria who do not sufficiently respond to standard therapy as recommended by existing guidelines.